2021
DOI: 10.1021/acs.inorgchem.1c02388
|View full text |Cite
|
Sign up to set email alerts
|

Tin(II)-Induced Large Birefringence Enhancement in Metal Phosphates

Abstract: Two alkali tin­(II) phosphates, namely, Rb­[SnF­(HPO4)] and Rb­(Sn3O)2(PO4)3, were synthesized through mild hydrothermal methods. They belong to the orthorhombic Pnma and Pbcn space groups, respectively. Rb­[SnF­(HPO4)] features a layered structure based on 1D [SnF­(HPO4)]∞ chains interconnected by hydrogen bonds, with Rb+ cations located at the interlayer space. For Rb­(Sn3O)2(PO4)3, each pair of [Sn3O]4+ clusters is bridged by a pair of [P(1)­O4]3– tetrahedra to build a 1D [Sn–P–O]∞ chain. These 1D [Sn–P–O]∞… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Traditionally, for the purpose of ensuring transparency in the UV region, alkali/alkaline earth metal cations are selected to design and synthesize UV optical crystals, which will eliminate the contribution of cationic polyhedra on the birefringence. [30][31][32][33][34][35][36][37][38][39] Herein, in addition to the Bi 3+ ions with stereochemically active lone pairs, a planar triangle π-conjugated [C(NH 2 ) 3 ] + group with a similar structural geometry to the [BO 3 ] 3− group was selected to substitute for traditional alkali/alkaline earth metal cations. This [C(NH 2 ) 3 ] + group possesses broad UV transparency and strong optical polarization anisotropy, which is beneficial to generate a large birefringence.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, for the purpose of ensuring transparency in the UV region, alkali/alkaline earth metal cations are selected to design and synthesize UV optical crystals, which will eliminate the contribution of cationic polyhedra on the birefringence. [30][31][32][33][34][35][36][37][38][39] Herein, in addition to the Bi 3+ ions with stereochemically active lone pairs, a planar triangle π-conjugated [C(NH 2 ) 3 ] + group with a similar structural geometry to the [BO 3 ] 3− group was selected to substitute for traditional alkali/alkaline earth metal cations. This [C(NH 2 ) 3 ] + group possesses broad UV transparency and strong optical polarization anisotropy, which is beneficial to generate a large birefringence.…”
Section: Introductionmentioning
confidence: 99%
“…Many attractive birefringent crystals activated by cations with stereochemically active lone pairs (SCALP) have been seen more in recent research. In addition to the mentioned Sn 2 PO 4 I (0.664 @546 nm) and SbB 3 O 6 (0.290 @546 nm), crystals of Sn 2 B 5 O 9 Br (0.439 @546 nm), K 2 Sb­(P 2 O 7 )F (0.157 @546 nm), α-NaSb 3 P 2 O 10 (0.121 @1064 nm), and Rb­[SnF­(HPO 4 )] (0.147 @1064 nm) also exhibit large birefringence . Usually, compounds constructed by tetrahedral units exhibit relatively small birefringence due to their poor anisotropy. , However, the compounds constructed by tetrahedral units are diverse, which form acentric structures and make contributions to many physical performances such as nonlinear optics .…”
mentioning
confidence: 99%
“…[13,83] On the whole, the birefringence increases gradually from Sn The series of crystals, X[SnF(HPO 4 )] (X = Rb, Na, NH 4 ) also show ideal optical anisotropy. [84] Rb[SnF(HPO 4 )] was obtained by Mao, et al, [84] while Gorbunova, et al reported the synthesis and crystal structure of M[SnF(HPO 4 )](M = NH 4 , Na). [85] Owing to the cation size effect, different from Na[SnF(HPO 4 )], Rb[SnF(HPO 4 )] is isomorphic with [NH 4 ]-[SnF(HPO 4 )] and crystallizes in Pnma space group.…”
Section: Sn II or Sb Iii Cooperated With Non-π-conjugated Po 4 Or Po 3 Fmentioning
confidence: 99%
“…The repulsion of the lone pair in combination with the smaller d Sn-Sn value induced the stereochemically active lone pairs in Rb[SnF(HPO 4 )] to align along the a axis, which is more conducive to producing a large birefringence in comparison with Na[SnF(HPO 4 )] (0.123@1064 nm). [84] Another Sn-based phosphate, P � 1-Sn 2 P 2 O 7 owns a large birefringence of 0.146@1064 nm. [13] The structural investigation of Sn 2 P 2 O 7 was carried out for the first time by Shpanchenko, et al using single crystal and powder X-ray diffraction.…”
Section: Sn II or Sb Iii Cooperated With Non-π-conjugated Po 4 Or Po 3 Fmentioning
confidence: 99%